Taurine in sports and exercise - Kurtz, J. A.; VanDusseldorp, T. A.; Doyle, J. A.; Otis, J. S. (Journal of the International Society of Sports Nutrition, 2021)
Background: Taurine has become a popular supplement among athletes attempting to improve performance. While the effectiveness of taurine as an ergogenic aid remains controversial, this paper summarizes the current evidence regarding the efficacy of taurine in aerobic and anaerobic performance, metabolic stress, muscle soreness, and recovery. Methods: Google Scholar, Web of Science, and MedLine (PubMed) searches were conducted through September 2020. Peer-reviewed studies that investigated taurine as a single ingredient at dosages of < 1 g - 6 g, ranging from 10 to 15 min-to-2 h prior to exercise bout or chronic dose (7 days- 8 weeks) of consumption were included. Articles were excluded if taurine was not the primary or only ingredient in a supplement or food source, not published in peer-reviewed journals, if participants were older than 50 years, articles published before 1999, animal studies, or included participants with health issues. A total of 19 studies met the inclusion criteria for the review. Results: Key results include improvements in the following: VO2max, time to exhaustion (TTE; n = 5 articles), 3 or 4 km time-trial (n = 2 articles), anaerobic performance (n = 7 articles), muscle damage (n = 3 articles), peak power (n = 2 articles), recovery (n = 1 article). Taurine also caused a change in metabolites: decrease in lactate, creatine kinase, phosphorus, inflammatory markers, and improved glycolytic/fat oxidation markers (n = 5 articles). Taurine dosing appears to be effective at ~ 1-3 g/day acutely across a span of 6-15 days (1-3 h before an activity) which may improve aerobic performance (TTE), anaerobic performance (strength, power), recovery (DOMS), and a decrease in metabolic markers (creatine kinase, lactate, inorganic phosphate). Conclusions: Limited and varied findings prohibit definitive conclusions regarding the efficacy of taurine on aerobic and anaerobic performance and metabolic outcomes. There are mixed findings for the effect of taurine consumption on improving recovery from training bouts and/or mitigating muscle damage. The timing of taurine ingestion as well as the type of exercise protocol performed may contribute to the effectiveness of taurine as an ergogenic aid. More investigations are needed to better understand the potential effects of taurine supplementation on aerobic and anaerobic performance, muscle damage, metabolic stress, and recovery.